CÉSAR VALLEJO: FROM THE POEM TO FILM - Yalán Dongo, Eduardo (2026)
This article examines the relationship between the literary work of César Vallejo—both poetry and drama—and cinema, arguing that the author develops a distinctive intermedial cinematic thought grounded in the concept of the “double.” Through a historical-critical framework, the study identifies a theoretical gap in the existing scholarship: the absence of a conceptual apparatus capable of articulating the transition from Vallejo’s literary production to the cinematic domain. To address this gap, the article proposes the concept of the “double” as a structuring principle, understood as a logic of doubling that configures aesthetic thought as a process of translation between media. Drawing on poetic texts, theatrical works (Lock-out, Colacho hermanos, La piedra cansada), and Vallejo’s unfinished film projects, the study reflects on how his writing assimilates cinematic procedures such as montage, visuality, gesture, and scenic simultaneity. In this sense, the double operates as the structural core of a hybrid aesthetics that exceeds generic boundaries, ultimately configuring a creative space between literature and the seventh art. The article concludes that Vallejo anticipates a conception of cinema as a total art form with a mass and humanistic vocation, in which his lyrical and dramatic impulses converge. Ultimately, this poetics of doubling reveals the revolutionary and inclusive character of his artistic project.